IDENTIFICATION OF CLIMATE RESILIENT GENOTYPES ON BASE OF PHYSIO-MORPHIC AND YIELD RELATED TRAITS IN MAIZE (ZEA MAYS L.) - AHMAD , K; ULLAH , A; ISLAM , B; KHAN , MA; QADIR , MS; SALEEM , S; AHMAD , I; REHMAN , ZU; HUSSAIN , S (Biological and Clinical Sciences Research Journal, 2024)
The impact of climate change on maize production is a growing concern. Changes in temperature, precipitation patterns, and the increased frequency of extreme weather events can significantly affect maize yields. Recognizing the importance of developing climate-resilient maize varieties, an experiment was conducted in 2022 to identify such genotypes. Ten commercial maize varieties were planted with three different sowing dates in the spring season: January 15th, January 30th, and February 15th. The results indicated that Sahiwal Gold and Malka 2016 were climate-resilient and produced high grain yields compared to other varieties across the three sowing dates. The findings concluded that the January 15th sowing date was the most effective, with genotypes producing the highest yields. Physio-morphic traits such as relative water content, chlorophyll content, days to tasseling, days to silking, plant height, and yield related traits ear length, and 100-kernel weight supported the plants in producing grain yield per hectare under changing climatic conditions. The variety Pop-1 was found to be susceptible to climate change, resulting in the lowest grain yield. The selected genotypes will be valuable in breeding programs aimed at developing climate-resilient maize varieties.